(untitled) - Henkes, Kevin ([New York], 2004)
When Kitten mistakes the full moon for a bowl of milk, she ends up tired, wet, and hungry trying to reach it.
Keywords: Cats; Fiction; Animals; Fiction; Infancy; Moon; Fiction